Violence against women: factors and effects: Analytical Theory Study - Abdullah, Muhammad Qasim; Alawi, Moh Araq (Al-Adab Journal, 2022)
The phenomenon of violence against women is one of the most dangerous negative phenomena that threaten the security and integrity of the family and society alike. Violence against women is one of the manifestations of unequal relations between men and women, which creates distorted forms of social relations, and turbulent patterns of behavior inside and outside the family. And if violence against women means the exercise of power that harms women, the research revealed different forms of violence against women, including physical, verbal, sexual and psychological, in addition to social chastity practiced by society and based on male preference over female. The research reached the following most important results: 1- Loss of self-confidence and self-capacity for women as a human being. 2- The general deterioration in the social, economic and national role and function of women. 3- Destruction of women’s humanity and humanity. 4- The inability to raise children and raise them in a proper educational manner. 5- Economic factors are one of the most common drivers of violence against women that many societies are witnessing at the present time, and the reason for this is due to the economic pressures that a large segment of society suffers from. 6-n the wrong interpretation of some religious texts is a factor of violence against women, as some tend Husbands have to understand the religious guidelines of the husband-wife relationship in a way that is consistent with their desires to impose their control or power over the wife.